Inhibitory Power Of Probiotics Drinks On The Streptococcus Mutans Growth - Rosida Intan Andica; Welly Anggarani; Andina Rizkia Putri Kusuma (Jurnal Medali, 2022)
Background: Streptococcus mutans is an oral cavity bacteria that is dominantly found. The acidogenic nature of bacteria can affect the damage to the physical and biochemical structures of dental biofilms. Streptococcus mutans growth becomes important to control. One way to control its growth is through the use of probiotic bacteria available in processed foods. The objective of this study is to investigate the effect of probiotic drinks against the Streptococcus mutans mutans. Method: This study is experimental research with a posttest-only group design, using two test groups. Streptococcus mutans suspension with McFarland turbidity standard of 0.5 in MRS Agar medium was placed on a paper disc that had been soaked in aqua dest (control group) or probiotic drink (treatment group) for ± 20 minutes and then incubated for 48 hours at 37oC. Each group was replicated 16 times. After incubation, the diameter of the Streptococcus mutans growth inhibition zone formed was measured using a caliper.Result: The control group did not show an inhibitory zone, while the treatment group resulted in a mean diameter inhibition zone of 1.18 mm. The Mann Whitney test proved that the treatment group had a significantly higher diameter of the inhibition zone compared to the control one (p=0.000).Conclusion: Probiotic drink had an inhibitory power on the Streptococcus mutans growth